Perilaku Birokrat Dalam Pelayanan Publik Di Distrik Asologaima Kabupaten Jayawijaya - Yoel Tabuni (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
In line with the rapid development of the times and the increasingly complex problems faced by the state, there has also been a development in government administration which has been marked by a shift in the paradigm of governance from Rule Governance. This situation makes the bureaucracy rigid, in an environment that is only limited to flowing the instructions or following instructions. The district government in an Asologaima District has the main task of carrying out part of the authority delegated by the district head in the fields of government, economy, and development, society, peace, and order as well as coordination.The method is sed is descriptive method. Bureaucrats as providers of public services must be able to provide quality services, the quality of service of bureaucrats to society is closely related to customer satisfaction or consumer satisfaction as the recipient of the service itself.